PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT. PRESTASI JAKARTA HEBAT DEPOK - Setiawan, Riki; Irwansyah (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the effect of training and career development on employee performance both partially and simultaneously at PT. Jakarta's Great Achievement Depok. This research method uses quantitative methods. The data collection methods used are primary and secondary data. The sampling technique used saturated sampling, and the sample obtained in this study was 54 respondents. Data analysis used SPSS version 26. The analysis techniques used were validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, coefficient of determination and hypothesis testing. Partially testing the hypothesis for the Training variable (X1) obtained tcount > ttable (7.451 > 1.675), and a significance value of 0.000 < 0.05. This means that Training (X1) has a significant effect on Employee Performance (Y). Partially testing the hypothesis for the Career Development variable (X2) obtained tcount > ttable (10.378 > 1.675). This means that Career Development (X2) has a significant effect on Employee Performance (Y). Simultaneous hypothesis testing obtained a value of fcount > ftable (58.666 > 3.179), and a significance value of 0.000 < 0.05. So it can be concluded that Training (X1) and Career Development (X2) simultaneously have a significant effect on Employee Performance (Y). The determination obtained by R square is 0.697, meaning that the Training and Career Development variables together have an influential contribution of 69,7% of employee performance. Meanwhile, the remaining 30,3% was influenced by other factors not researched by the author.